Prospective study on the incidence and progression of clinical signs in naïve dogs naturally infected by Leishmania infantum. - Valentina Foglia Manzillo; Trentina Di Muccio; Sivia Cappiello; Aldo Scalone; Rosa Paparcone; Eleonora Fiorentino; Manuela Gizzarelli; Marina Gramiccia; Luigi Gradoni; Gaetano Oliva (Public Library of Science (PLoS), 2013)
The incidence of clinical and clinicopathological signs associated with the progression of infection was evaluated prospectively in 329 naïve young dogs exposed to Leishmania infantum transmission and examined periodically during 22 months (M). The dogs were part of Leishmania vaccine investigations performed under natural conditions. Vaccinated groups were considered in the evaluation when the vaccine resulted non-protective and the appearance and progression of signs did not differ statistically from controls at each time point, otherwise only control groups were included. 115 beagles were part of 3 studies (A to C) performed in the same kennel; 214 owned dogs (29 breeds, 2.3% beagles) were included in a study (D) performed in 45 endemic sites. At M22 the prevalence of any Leishmania infection stage classified as subpatent, active asymptomatic, or symptomatic was 59.8% in studies A-C and 29.2% in study D. Despite different breed composition and infection incidence, the relative proportion of active infections and the progression and type of clinical and clinicopathological signs have been similar in both study sets. All asymptomatic active infections recorded have invariably progressed to full-blown disease, resulting in 56 sick dogs at M22. In these dogs, lymph nodes enlargement and weight loss--recorded from M12--were the most common signs. Cutaneous signs were seen late (M18) and less frequently. Ocular signs appeared even later, being sporadically recorded at M22. Most clinicopathological alterations became evident from M12, although a few cases of thrombocytopenia or mild non-regenerative anemia were already observed at M6. Albumin/globulin inversions were recorded from M12 and urea/creatinine increase appeared mostly from M18. Altogether our findings indicate that any susceptible young dogs naturally infected by L. infantum present a common pattern of progression of signs during 2 years post infection, providing clues for medical and epidemiological applied aspects.